2021
DOI: 10.1057/s41267-021-00465-8
|View full text |Cite
|
Sign up to set email alerts
|

Foreignness research in international business: Major streams and future directions

Abstract: Foreignness has long been a central construct in international business research, with research streams examining its conceptualizations, manifestations, and consequences. Researchers started by taking foreignness to be a liability, then later considered the possibility of its being an asset. A still more recent view is that foreignness is an organizational identity that a firm can purposefully manage. Broadly conceived, foreignness is an umbrella construct that directly or tangentially covers research on coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 248 publications
(501 reference statements)
0
16
0
2
Order By: Relevance
“…We argue that there are variations in the advantage and disadvantage created by the country of origin on firm’s investments. Most studies focus on their liability of being foreign, with fewer studies that focus on their advantage of being foreign at the multinational firm and subsidiary levels (Caussat, 2019 ; Hymer, 1976 ; Lu et al, 2022 ; Zaheer, 1995 ). By taking into account the different actors in the host country, in this case, the government and consumers, we argue that the liability and advantage depend on how these actors view the same country of origin of foreign firms relative to other foreign firms, rather than whether they are foreign or non-foreign.…”
Section: Contributionsmentioning
confidence: 99%
See 3 more Smart Citations
“…We argue that there are variations in the advantage and disadvantage created by the country of origin on firm’s investments. Most studies focus on their liability of being foreign, with fewer studies that focus on their advantage of being foreign at the multinational firm and subsidiary levels (Caussat, 2019 ; Hymer, 1976 ; Lu et al, 2022 ; Zaheer, 1995 ). By taking into account the different actors in the host country, in this case, the government and consumers, we argue that the liability and advantage depend on how these actors view the same country of origin of foreign firms relative to other foreign firms, rather than whether they are foreign or non-foreign.…”
Section: Contributionsmentioning
confidence: 99%
“…However, these studies pay little attention to how the country of origin affects firms themselves (Yu & Liu, 2018 ). On the other hand, the literature on the liability of foreignness focuses on the firm level and typically argues that subsidiaries of multinational firms face a competitive disadvantage as they incur additional costs that host-country firms do not (Caussat et al, 2019 ; Hymer, 1976 ; Zaheer, 1995 ; for a recent review, see Lu et al, 2022 ). A later literature discussed the advantage of foreignness that subsidiaries of foreign firms enjoy over domestic firms because of their privileged access to foreign technology (Nachum, 2010 ; Un, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In international management, distance is mostly seen as being an element of liability of foreignness (Rugman, Verbeke, & Nguyen, 2011), though some authors have challenged this notion and suggested concepts such as "friction" (Shenkar, 2001;Shenkar et al, 2008;Shenkar, 2012), "liability of outsidership" (Johanson & Vahlne, 2009), or "liability of newness and smallness" (Puthusserry, Child, & Rodrigues, 2014) instead. These new metaphors have themselves also been criticized for conveying negative effects of difference (Drogendijk & Zander, 2010), since foreignness can also be an asset for a company (Edman, 2016;Lu, Ma, & Xie, 2021).…”
Section: Distance In Managementmentioning
confidence: 99%